Our missing hearts : [large type] a novel - Ng, Celeste (Reese's book club., 2022)
In a society consumed by fear, twelve-year-old Bird Gardner, after receiving a mysterious letter, sets out on a quest to find his mother, a Chinese-American poet who left when he was nine years old, leading him to New York City, where a new act of defiance may be the beginning of much-needed change.